The Practice of Learning Community on Teachers’ Development: A Case of Indonesia - Evitha Soraya; Supadi Supadi (STAI Hubbulwathan Duri, 2022)
This article aims to evaluate the programs organised by a professional learning community in Indonesia, MGMP (Subject Teacher Conference), as a forum for teachers' professional development with two principles: communal deliberation and subject teachers. Forty teachers were randomly selected and surveyed (N = 40), and three school inspectors were interviewed (N = 3). This recent study employed a mixed-method design. Furthermore, a content analysis was carried out to study the standards of MGMP development. Findings revealed that the programs have been consistent with the underlying principles of MGMP and are effective for Social Science teachers' development. Although more attention should be given to teachers' real performance in classes, the researchers believe regular meetings have provided teachers with opportunities to exchange ideas, discover solutions, and create a pool of current information and valuable experiences. The communal deliberation is contextual to the practice of PLC in Indonesia. It never changes the goal objective to improve teachers' professional development to improve student's quality of learning. It strengthens the spirit of collegiality in teachers' cooperation and collaboration.